Prevalence of foodborne viruses and influenza A virus from poultry processing plants to retailed chickens - Yeo, Daseul; Song, Mengxiao; Hossain, Md. Iqbal; Jung, Soontag; Wang, Zhaoqi; Seo, Dong Joo; Rhee, Min Suk; Choi, Changsun (Frontiers in Sustainable Food Systems, 2023)
Foodborne viruses are a serious concern in public health. This study investigated the prevalence of eight foodborne viruses (norovirus (NoV), adenovirus (AdV), sapovirus (SapoV), astrovirus, hepatitis A virus (HAV), hepatitis E virus (HEV), rotavirus, and aichivirus) and influenza A virus (IAV). A total of 316 chicken samples were collected from three poultry processing plants to commercial markets (local and online). RT-qPCR and PCR-positive amplicons obtained from monitoring were confirmed by sequence analysis. Foodborne viruses and IAV were not found in poultry processing plants. Of the 100 chickens purchased from the local and online markets, 19 (19.0%) of AdV and 2 (2.0%) of SapoV were detected. NoV, astrovirus, HAV, HEV, rotavirus, aichivirus, and IAV were not detected in the retailed chickens. Phylogenetic analysis identified eighteen human AdV-41, one porcine AdV, and two SapoV-GI.1. It was the first case of the discovery of the SapoV gene in chicken. The average contamination level of detected AdV was 2.4 log RNA copies/g, but there were cases where the highest level was 5.35 log RNA copies/g. This study highlights the importance of chicken’s contribution to the transmission of AdV with the possibility of annual variability with emerging symptoms. The prevention of AdV contamination in the food chain from slaughterhouses to retail markets should be monitored and controlled in further study.